2021
DOI: 10.3389/fonc.2021.582788
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Analysis Based on Contrast-Enhanced MRI for Prediction of Therapeutic Response to Transarterial Chemoembolization in Hepatocellular Carcinoma

Abstract: PurposeTo investigate the role of contrast-enhanced magnetic resonance imaging (CE-MRI) radiomics for pretherapeutic prediction of the response to transarterial chemoembolization (TACE) in patients with hepatocellular carcinoma (HCC).MethodsOne hundred and twenty-two HCC patients (objective response, n = 63; non-response, n = 59) who received CE-MRI examination before initial TACE were retrospectively recruited and randomly divided into a training cohort (n = 85) and a validation cohort (n = 37). All HCCs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 45 publications
4
19
0
Order By: Relevance
“…7 Recently, several radiomic models have been developed to estimate the response of TACE treatments that have shown promising results. [8][9][10] Chen et al built a clinical radiomics model that showed good performance in predicting the response of treatment to the first TACE in patients with intermediate-stage HCC, with the area under the receiver operator characteristic curve (AUC) reaching up to 0.94. 8 Kong et al developed an MRI-based radiomics model to predict tumor response after TACE in intermediateadvanced patients with HCC.…”
Section: Introductionmentioning
confidence: 99%
“…7 Recently, several radiomic models have been developed to estimate the response of TACE treatments that have shown promising results. [8][9][10] Chen et al built a clinical radiomics model that showed good performance in predicting the response of treatment to the first TACE in patients with intermediate-stage HCC, with the area under the receiver operator characteristic curve (AUC) reaching up to 0.94. 8 Kong et al developed an MRI-based radiomics model to predict tumor response after TACE in intermediateadvanced patients with HCC.…”
Section: Introductionmentioning
confidence: 99%
“…TACE is recognized as an effective treatment for advanced HCC ( 125 ), but its long-term efficacy needs to be further improved ( 139 141 ). MRI radiomics can be used to predict the response to TACE treatment and provide a reference for the formulation of individualized treatment plans ( 21 , 22 , 142 148 ). Sun et al ( 142 )predicted the risk of early postoperative progression based on multiparameter MRI data before TACE.…”
Section: Prediction Of Response To Tacementioning
confidence: 99%
“…TACE is recognized as an effective treatment for advanced HCC (125), but its long-term efficacy needs to be further improved (139)(140)(141). MRI radiomics can be used to predict the response to TACE treatment and provide a reference for the formulation of individualized treatment plans (21,22,(142)(143)(144)(145)(146)(147)(148)…”
Section: Prediction Of Response To Tacementioning
confidence: 99%
See 1 more Smart Citation
“…Random forest (RF) is regarded as one of the most promising ML algorithm 10 , and it is consisted of an ensemble learning approach of multiple unique decision trees. Although RF algorithm has previously been utilized to predict the prognosis of HCC patients after various treatment modalities 11 - 15 , it has not yet been used to predict the early TACE refractoriness. Therefore, the purpose of the present study is to develop and validate a predictive model of early TACE refractoriness based on an RF algorithm.…”
Section: Introductionmentioning
confidence: 99%